BIOMECHANICS ANALYSIS: THE IMPACT OF BACKSWING ANGLE ON ACCURACY AND DISTANCE OF SHOTS IN WOODBALL ATHLETES AT UNIVERSITAS NEGERI JAKARTA - Hermawan, Iwan; Ihsani, Sri Indah; Hardjanto, Vannes Arafah Putra (MEDIKORA, 2025)
The purpose of this study was to determine whether there is a backswing angle that has the greatest impact on shot distance and whether it influences long shot distance in woodball. Woodball players from Jakarta State University who trained for two to three years participated in this study. Examine the connection between the dependent variable (long stroke distance) and the independent variable (backswing angle). This study will employ an experimental research design and associative quantitative research methods. After using Kinovea software to assess the backswing angle and stroke distance, SPSS 25.0 software was used for processing. The study's findings indicate that the backswing angle affects long shot distance, as indicated by the Wilcoxon Ranked Test's non-parametric statistical test results (p < 0.05) and Z value of -4.016. This indicates that the influence is substantial. However, the second stroke, which has a distance of 39.99 meters and an angle of 118◦, has a Z value of -2.384 and a significant value of p-value = 0.017 < 0.05. This indicates that there is an effective backswing angle to affect the shot's distance. Thus, this study demonstrates the existence of an angle. This study aids in the development of fundamental woodball skills, particularly in enhancing players' long-shot prowess. These results can serve as the foundation for developing a structured training regimen that emphasizes biomechanical elements that can increase punching efficacy and accuracy. Athletes can use this information to increase their performance and backswing angle, which will make their stroke more efficient and effective. With training planning, trainers can use this data as a reference to help athletes improve their long strokes.